Implementation of Subsidized Fertilizer Policy in Increasing Rice Harvests in Rural Communities - Sari, Ade Risna; Titin, Titin; Pareira, Magdalena Sunarty; Fkun , Egidius; Ekobelawati , Fransiska (Journal Of Human And Education (JAHE), 2024)
Subsidized Fertilizer policy is a strategic policy to encourage increased production and productivity in the agricultural sector. Fertilizer subsidies encourage agricultural specialization and increase agricultural output, and directly affect farmer income, while income can be increased through agricultural productivity from subsidies. This community service was carried out in Gemba Jaya Village, Sintang, West Kalimantan. In obtaining the data used were observation and literature review. This service activity is an effort to implement the subsidized fertilizer policy in Gemba Jaya Village. This effort was motivated by the unmet need for subsidized fertilizer in Gemba Jaya Village, which resulted in suboptimal rice production results. As a form of the author's thoughts, several efforts and breakthroughs have been offered, that is agricultural intensification is an effort made to increase agricultural output by: 1.) Optimizing available agricultural land will focus on efforts to address problems related to land management, 2.) Procurement of superior seeds, planting, fertilizing, 4.) Eradicating pests and diseases in plants, 5.) Harvesting and post-harvest activities to obtain increased rice production.